The Living Landscape of Il grande ritratto - Malvestio, Marco (Quaderni d'Italianistica, 2022)
This essay discusses Dino Buzzati’s Il grande ritratto (Larger than Life) in the theoretical coordinates provided by ecocritical reflections on science fiction. Examining the science fictional dimension of Il grande ritratto is useful both to underline the close ties the author had with the genre from a historical perspective, and to highlight the possibilities presented by science fiction in terms of the representation of technological innovations and the environment. By analyzing the nature-technology hybrid in Il grande ritratto, the essay highlights how Buzzati’s notion of the agency of matter betrays an ecophobic attitude (which is to say, a fear of the agency of nature) that is intertwined with a similar fear of female agency, due to the identification of the landscape with a female artificial intelligence.